Ice-albedo tipping points in a diffusive energy-balance model with land and ocean - Hilbertsen, Kristian Bergum (UiT Norges arktiske universitet, 2021)
The ice-albedo feedback is associated with the nonlinearity in the climate system, due to the sudden change in albedo between ice-free and ice-covered surfaces. This nonlinearity can potentially cause abrupt and dramatic shifts in the climate, referred to as tipping points. It is also believed that this mechanism has contributed significantly to the precipitous losses of Arctic sea ice, which have outpaced the projections of most climate models. This feedback mechanism has been studied since at least the nineteenth century, and it has had a major role in climate science ever since. The tipping points that result from this mechanism has changed the way we view the history of the Earth with the introduction of, among other things, the snowball Earth hypothesis. In this thesis we will introduce land area to a diffusive Energy Balance Model, and study these critical transitions. We will also test for Early Warning signals for these tipping points.